Pengaruh Kompetensi, Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Kecamatan Taliwang Kabupaten Sumbawa Barat - Nuraini; Sri Rahayu (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
This study examines the factors that influence employee performance at the Taliwang Sub-district Office, West Sumbawa Regency, with a focus on competence, leadership, and work discipline. Optimal employee performance is crucial for the effectiveness of public services and the success of regional development. The purpose of this study is to analyze the influence of competence, leadership, and work discipline on employee performance at the office. A quantitative method was used to collect primary data through questionnaires. The population consisted of all employees at the Taliwang Sub-district Office, with total sampling applied in selecting respondents. Data analysis was conducted using multiple linear regression to test the relationship between independent variables and the dependent variable based on data obtained from the questionnaires. The results of the study show that competence, leadership, and work discipline have a positive and significant influence on employee performance. Adequate competence enables employees to complete tasks more effectively and efficiently. Effective leadership creates a supportive work environment and motivates employees. Good work discipline enhances employees’ responsibility and commitment to their work. This study concludes that competence, leadership, and work discipline are important factors in improving employee performance at the Taliwang Sub-district Office. The implications of this research highlight the need for continuous efforts to develop employee competence, strengthen leadership, and enforce work discipline in order to improve the quality of public service.